2015
DOI: 10.1002/ddr.21277
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MicroRNAs in Prevention and Treatment of Neurodegenerative Disorders

Abstract: Preclinical Research microRNAs (miRNAs) are small noncoding RNAs (ncRNAs) that are key regulators of gene expression. They act on wide range of targets by binding to mRNA via imperfect complementarity at 3' UTR. Evidence suggests that miRNAs regulate many biological processes including neuronal development, differentiation, and disease. Altered expression of several miRNAs has been reported in many neurodegenerative disorders (NDDs). Many miRNAs are altered in these diseases, but miRNA 15, miRNA 21, and miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 136 publications
0
25
0
Order By: Relevance
“…Concordance between these two works suggests a potential role of miRNAs as therapeutic targets to regulate dysregulated mRNAs expression. Indeed, some studies had previously examined the involvement of a miRNA network in neurodegenerative diseases (Hebert and De Strooper, 2009; Lau et al, 2013; Ubhi et al, 2014) and demonstrated the possibility to target miRNAs to treat neurodegenerative disorders (Gupta et al, 2015; Weinberg and Wood, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Concordance between these two works suggests a potential role of miRNAs as therapeutic targets to regulate dysregulated mRNAs expression. Indeed, some studies had previously examined the involvement of a miRNA network in neurodegenerative diseases (Hebert and De Strooper, 2009; Lau et al, 2013; Ubhi et al, 2014) and demonstrated the possibility to target miRNAs to treat neurodegenerative disorders (Gupta et al, 2015; Weinberg and Wood, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…They tend to repress genes’ expression level through binding to specific sequences mostly located in the 3'‐untranslated region (3'UTR) of mRNAs, culminating in mRNA degradation or deadenylation and translation inhibition . miRNAs have an enormous modulatory potential considering that each single miRNA can govern expression of hundreds of different transcripts and that's why whole phenotype of a disease can be feasibly affected by regulating a single miRNA molecule . Mounting evidence has emerged showing the association between miRNA network and pathogenesis of neurodegenerative disorders including PD .…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence has emerged showing the association between miRNA network and pathogenesis of neurodegenerative disorders including PD . Furthermore, altered level of several miRNAs has been reported in disparate PD models and human brains of patients suffering from PD . While there is substantial literature confirming miRNAs’ implication in PD development, only a few studies have attempted to identify deregulated miRNAs …”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of miRNA in the pathophysiology of polyQ disorders miRNA dysregulation is emerging as a critical factor contributing to neurodegeneration [105][106][107][108][109][110][111][112]. Major alterations in brain mRNA levels have been observed in various neurodegenerative disorders, and as mentioned above, altered neuronal transcriptional activity is a persistent feature of most polyQ disorders.…”
Section: Histone Modifications and Chromatin Remodeling In Polyq Disordersmentioning
confidence: 99%